An exploratory study of strata residential properties problems in Peninsular Malaysia and how they are resolved - Mohamad, Nor Asiah (Korean Housing Association, 2015)
This study identifies the common problems faced by the owners of strata titles, the Management Corporation, the Joint Management Body, the Commissioner of Building (COB) as well as the Managing Agent being the stakeholders in managing strata properties. The methods employed are qualitative in nature. Analysis is done based on reports published by the relevant authorities dealing with strata residential properties as well as the case law as reported in the two leading journals in Malaysia i.e. the Malayan Law Journal and the Current Law Journal. The types and nature of problems are derived from the annual reports. The extent of the problems is determined based on the figures and supported by observation and interviews with the COB, being the agency directly involved in overseeing and monitoring strata properties management. The findings show that a substantial number of problems exist in the management of strata properties despite a law that allows the owners to self-managed their own properties. Having stated the status quo concerning the problems, the study also looks at the various means of resolving disputes as exist under the Malaysian housing system. The study proposes that alternative dispute resolution (ADR) modes are more appropriate in ensuring the sustainability of strata living and management.